Sociological Study of the Images of the Neighboring Countries: Russian Student Youth Stereotypes, and Their Contextual Frames - Trotsuk, Irina V. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
The article identifies three basic ‘dimensions’ of the youth social mood. The first dimension is formed by a set of various cognitive, affective and behavioral orientations (and the patriotic mood is an integral part of this complex). The second dimension is formed by a set of estimates of the macro-social context of life in one’s country. The third dimension is constituted by geopolitical awareness, i.e. the images of the neighboring countries. All three dimensions are difficult to measure due to the multiplicity of their conceptualization frames and excessive connotations of the basic terminology. The author provides an overview of the results of a series of surveys conducted in 2009-2013 on the samples of Moscow students by the Sociological Laboratory of the Peoples’ Friendship University of Russia to show what data we can obtain with the help of qualitative approach in ‘measuring’ these dimensions of the youth worldview and social mood, especially in identifying the common images of the neighboring countries (on the example of China, Kazakhstan and Serbia). The author focuses on technical and substantial details of the surveys, and concludes with recognizing the necessity of revealing social representations and stereotypes of public opinion in cross-cultural and comparative perspectives.